The Analysis of Student’s Exam Anxiety and Its Effects on Psychological Reaction - Arnita, Fitri; Netrawati, Netrawati; S, Neviyarni; Marjohan, Marjohan (Jurnal Aplikasi IPTEK Indonesia, 2022)
Exams are a common activity at school, and students commonly experience anxiety related to exams. This study attempts to provide a general understanding of exam anxiety. This kind of study use quantitative descriptive research techniques and a test anxiety questionnaire as a tool for gathering data. The study's participants were SMAN 13 Padang students. Simple random sampling was used to select the subjects. This study combines descriptive analysis with data analysis tools. The findings of this study suggest that exam anxiety has a variety of manifestations. Each aspect has a different percentage; the emotional reaction aspect, which is the largest, falls into the high category, with a percentage of 38.9%; the cognitive reaction aspect, which is the highest, has a percentage of 53.7%; and the physiological reaction aspect, which is the largest, falls into the medium category, with a percentage of 37.9%. These findings suggest that many respondents struggle with exam anxiety. In order for attempts to combat and avoid exam anxiety, Counselling Guidance Teachers and Counsellors will use this research as information.